ANALISIS RESILIENSI FINANSIAL: PERAN MODAL SOSIAL, SUMBER DAYA EKONOMI, DAN PERILAKU KEUANGAN DALAM MENGHADAPI KERENTANAN - Naufal Afif; Nur Hidayah; Martiana Riawati Utami (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to map the level of individual financial resilience in the Kedu area based on the Financial Resilience Spectrum category, which includes four levels: severe financial vulnerability, high financial vulnerability, low financial vulnerability, and financially resilient. This study uses a survey method with a purposive sampling approach, involving 47 respondents domiciled in the Kedu area. The research instrument is based on four components of financial resilience: economic resources, financial products and services, financial knowledge and behavior, and social capital. The results show that the average financial resilience of respondents is at low vulnerability with a value of 2.53, with the social capital component contributing the highest to the overall value, while the financial knowledge and behavior component is in the lowest position. Complementing the analysis, a comparison between respondents with various income levels was also carried out. The results of this study are relevant for policy makers, financial institutions, and community organizations to design interventions that support increased financial resilience, especially for vulnerable groups.